2011
DOI: 10.1002/jrs.3120
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman study of exfoliated Bi2Sr2CaCu2O8+δ single crystals with different thicknesses

Abstract: Exfoliated Bi2Sr2CaCu2O8+δ (Bi‐2212) single crystals were prepared by micromechanical cleavage of bulk Bi‐2212 single crystals on SiO2/Si substrates. Room temperature micro‐Raman spectra were collected using a 532‐nm laser source. The evolutions of the spectra of A1g (Bi), A1g (Sr), and A1g (OBi) Raman modes with different thicknesses of the samples were studied. The refractive index of Bi‐2212 single crystal was obtained by studying the intensity evolutions based on the interference effect. The observed waven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
(32 reference statements)
4
11
0
Order By: Relevance
“…First, TEM studies have demonstrated that BSCCO 2D atomic crystals are monocrystalline and have the same crystal structure as bulk [4]. This was further confirmed by Raman scattering and X-ray Laue microscopy experiments [16,19,20]. Raman scattering selection rules (i.e.…”
Section: Sample and Experimental Detailsmentioning
confidence: 94%
See 1 more Smart Citation
“…First, TEM studies have demonstrated that BSCCO 2D atomic crystals are monocrystalline and have the same crystal structure as bulk [4]. This was further confirmed by Raman scattering and X-ray Laue microscopy experiments [16,19,20]. Raman scattering selection rules (i.e.…”
Section: Sample and Experimental Detailsmentioning
confidence: 94%
“…Translational symmetry means that only q = 0 processes can be observed, while point group symmetry impose certain polarization dependences. In a previous unpolarized Raman study [19], Wang et al studied scattering due to phonons as a function of thickness. They found that the number and frequency of these modes was unchanged with thickness, meaning that the lattice translational symmetry and dynamics are unperturbed in exfoliated BSCCO.…”
Section: Sample and Experimental Detailsmentioning
confidence: 99%
“…Wang et al . carried out a micro‐Raman study of exfoliated Bi 2 Sr 2 CaCu 2 O 8 single crystals with different thicknesses …”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Table III shows the optical constants, n and κ, at 532 nm obtained using the methods described above, along with derived quantities and previously published values. The refractive index values obtained using the linewidth-shift ratio range from 1.8 to 2.0 and are within ≤ 10% of those determined using a combined reflectanceellipsometry method [6], reflectance spectroscopy [10], and optical interference [9]. In contrast, Eq.…”
Section: Optical Propertiesmentioning
confidence: 57%
“…Furthermore, there is significant variation in these values. Two independent measurements of refractive index at 532 nm have also been reported [9,10] but only in one case was the direction of light propagation specified [10]. A similar situation exists with regard to the elastic properties with only two groups reporting values of elastic constants.…”
Section: Introductionmentioning
confidence: 88%